Affective Adaptation to Repeated SIT and MICT Protocols in Insulin-Resistant Subjects - Saanijoki T; Nummenmaa L; Koivumaki M; Loyttyniemi E; Kalliokoski KK; Hannukainen JC (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Introduction The aim of this study was to investigate affective responses to repeated sessions of sprint interval training (SIT) in comparison with moderate-intensity continuous training (MICT) in insulin-resistant subjects.Methods Twenty-six insulin-resistant adults (age, 49 (4) yr; 10 women) were randomized into SIT (n = 13) or MICT (n = 13) groups. Subjects completed six supervised training sessions within 2 wk (SIT session, 4-6 x 30 s all-out cycling/4-min recovery; MICT session, 40-60 min at 60% peak work load). Perceived exertion, stress, and affective state were assessed with questionnaires before, during and after each training session.Results Perceived exertion, displeasure, and arousal were higher during the SIT compared with MICT sessions (all P < 0.01). These, however, alleviated similarly in response to SIT and MICT over the 6 d of training (all P < 0.05). SIT versus MICT exercise increased perceived stress and decreased positive affect and feeling of satisfaction acutely after exercise especially in the beginning of the intervention (all P < 0.05). These negative responses declined significantly during the training period: perceived stress and positive activation were no longer different between the training groups after the third, and satisfaction after the fifth training session (P > 0.05).Conclusions The perceptual and affective responses are more negative both during and acutely after SIT compared with MICT in untrained insulin-resistant adults. These responses, however, show significant improvements already within six training sessions, indicating rapid positive affective and physiological adaptations to continual exercise training, both SIT and MICT. These findings suggest that even very intense SIT is mentally tolerable alternative for untrained people with insulin resistance.